An English Queen and Stalingrad The Story Of Elizabeth Angela Marguerite Bowes-Lyon (1900-2002). - Kulishenko, Natalia (Glagoslav Publications Ltd, 2020)
The author traces the Queen Mother's formative years, her family life in the palace environment, her growing adoration and ascension to the British throne, how she arranged aid to Stalingrad...